The Nature and Scope of Restitution. - Jaffey, Peter (Hart Pub., 2000)
This work advances a view of the framework of fundamental principles underlying the law of restitution which offers a means of understanding the tangle of conflicting authorities, and then proceeds to examine the case law in the light of it.